Strategic Planning and Performance of Telecommunication Companies in Rwanda (International Journal of Scientific Research and Management (IJSRM), 2022)
This research sought to examine the strategic planning practice as tool for performance in the telecommunication companies. Strategic planning for that reason offers a much-needed basis on which telecommunication companies can grow and evaluate its success against failures and establish boundaries for efficient decision-making. The research further assessed the level of influence of legal and regulatory framework as a moderating factor on the performance of Telecommunication industry in Rwanda. This study utilized both qualitative and quantitative data as well as applied a descriptive survey design. The study population included the 42 Top and middle level, managers of mobile phone operator companies in Rwanda which comprised of MTN and Airtel company Headquarter and different branches within Kigali City. The data collection instruments were pre-tested using the Cronbach’s alpha and factor analysis of dimensions reductions to determine the validity and reliability of the tests. The data collected was analyzed and presented using tables, by help of the SPSS statistical Package for Social Science. The results on, reliability test, descriptive statistics, demographic information of respondents, correlation analysis, normality test, heteroskedasticity test, factor analysis and regression results were established on all the variables of strategic planning, plus the intervening variable of the legal and regulatory framework. Notably, the correlation results revealed that Strategic Planning had a positive and significant. The results revealed that Strategic Planning has a positive and significant moderate relationship with Performance of Telecommunication industry. The results on linearity test for strategic planning and performance of the telecommunication industry since the level of linear association was found to be 0.953 which was also positive and statistically significant. Similarly, the null hypothesis Strategic Planning and performance of the telecommunications industry were subjected to the hypothesis to determine whether to accept or reject the null hypothesis and the results showed a positive and significant association between Strategic Planning and Performance of Telecommunication industry (β = 0.953, ρ< .05). Therefore, the hypothesis was rejected. Thus, as the Performance of Telecommunication industry increased, the strategic planning too increased. It can therefore be concluded that, the companies benefited tremendously when the strategic planning was taken into account for the efficient performance of the telecommunication industry in Rwanda.